(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The three pillars of India’s democratic system are the legislative, administration, and judicial, with their respective authorities and duties explicitly defined in the constitution. However, the debate rages on, particularly when it comes to the nomination of judges by the administration and judiciary. Following the adoption of the Constitution, the administration had a major voice in appointing judges. Later, the judiciary interpreted the Constitutional requirements and created the collegiums system, which limits the executive’s role in appointing judges to the higher courts. The judiciary’s standing was reinforced by the removal of the executive role. The purpose of this article is to analyze the Constitutional Provision, the function of the executive branch, as well as the importance of legal interpretations in the selection of justices.